2016
DOI: 10.3892/ijo.2016.3506
|View full text |Cite
|
Sign up to set email alerts
|

Slit2 and Robo1 induce opposing effects on metastasis of hepatocellular carcinoma Sk-hep-1 cells

Abstract: The neural guidance molecular, Slit2, and its cognate receptor, Robo1, play critical roles in the development of the nervous system, nevertheless, their functions are not limited to this system. Numerous studies have shown decreased Slit2 expression in a wide variety of cancers, highlighting its potential as a tumor suppressor. However, the Slit2/Robo1 signaling axis was reported to induce either suppressive or stimulatory effects on tumor growth and metastasis, depending on cellular context. There is a paucit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 42 publications
(52 reference statements)
1
12
0
Order By: Relevance
“…We and Kong et al showed that in lung cancer, Slit2/Robo1 inhibited lung cancer cell migration via inhibiting the Myob/RhoA signaling pathway 50. Meanwhile, Yuan, M et al showed high expression of slit2 and down-regulation of Robo1 markedly enhanced migration of hepatic cancer cell 104. The authors demonstrated that Robo1 overexpression upregulated matrix metalloproteinase (MMP)-2, MMP-9, and membrane-type1 MMP (MT1-MMP) expression, thereby promoting tumor metastasis 104.…”
Section: Roles Of Slit/robo In Cell Motilitymentioning
confidence: 99%
See 1 more Smart Citation
“…We and Kong et al showed that in lung cancer, Slit2/Robo1 inhibited lung cancer cell migration via inhibiting the Myob/RhoA signaling pathway 50. Meanwhile, Yuan, M et al showed high expression of slit2 and down-regulation of Robo1 markedly enhanced migration of hepatic cancer cell 104. The authors demonstrated that Robo1 overexpression upregulated matrix metalloproteinase (MMP)-2, MMP-9, and membrane-type1 MMP (MT1-MMP) expression, thereby promoting tumor metastasis 104.…”
Section: Roles Of Slit/robo In Cell Motilitymentioning
confidence: 99%
“…Meanwhile, Yuan, M et al showed high expression of slit2 and down-regulation of Robo1 markedly enhanced migration of hepatic cancer cell 104. The authors demonstrated that Robo1 overexpression upregulated matrix metalloproteinase (MMP)-2, MMP-9, and membrane-type1 MMP (MT1-MMP) expression, thereby promoting tumor metastasis 104. In malignant melanoma, MMP2 and MMP14 was showed to be downregulated by Slit3/Robo2 and thereby inhibiting cancer cell migration 105.…”
Section: Roles Of Slit/robo In Cell Motilitymentioning
confidence: 99%
“…ROBO1 is overexpressed in HCC samples [38]. Overexpression of ROBO1 could promote HCC cell growth and metastasis both in vitro and in vivo [39]. STC2 is upregulated in HCC, thereby facilitating HCC proliferation and survival as well as mediating chemotherapeutic resistance [40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…Slit2/Robo1 signaling has been associated with Akt phosphorylation and upregulation of β-catenin activity [25,26]. Yuan et al found Slit2/Robo1 promotes tumor invasion partly by upregulation of MMP2 after activation of PI3K/Akt signaling pathway in human hepatocellular carcinoma cell line [25].…”
Section: Discussionmentioning
confidence: 99%
“…Slit2/Robo1 signaling has been associated with Akt phosphorylation and upregulation of β-catenin activity [25,26]. Yuan et al found Slit2/Robo1 promotes tumor invasion partly by upregulation of MMP2 after activation of PI3K/Akt signaling pathway in human hepatocellular carcinoma cell line [25]. PI3K/Akt/ β-catenin signaling is highly activated in NPC [27] Activation of the PI3K/Akt signaling pathway results in aberrant cell proliferation, tumorigenesis and metastatic competence [28][29][30].…”
Section: Discussionmentioning
confidence: 99%